Pengaruh Penerapan Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Perusahaan : (Studi Kasus KSP XYZ) - Novrianni Agnes Monika Sinurat; Irawan Irawan; Evi Yuniarti (Pusat Riset dan Inovasi Nasional, 2024)
Nowadays, business development is increasingly complex and competitive, therefore companies must improve their performance. In an effort to improve company performance, the accounting information system (AIS) and internal control system (SPI) are very influential, because good implementation of SIA will make the tasks carried out by all employees easier. Therefore, this research aims to determine the effect of implementing AIS and SPI on the performance of the XYZ Savings and Loans Cooperative (KSP) case study company. The data used is primary data, this data was obtained through distributing questionnaires. The population and sample in this study were all KSP XYZ employees, namely 33 people spread across four branch offices. The method used is multiple linear regression analysis using the SPSS Version 29 test tool. Based on the research that has been carried out, the results show that partially SIA and SPI have no effect on company performance and, simultaneously, SIA and SPI have an effect on company performance.